Evaluasi Pembelajaran Daring Materi Sepaktakraw pada Siswa Kelas VII (Universitas Negeri Semarang, 2022)
The The purpose of this study was to determine the success of online learning, especially the learning material of sepak takraw in seventh grade students at SMP Negeri 2 Cilongok. This study uses a descriptive qualitative approach. The subject of this research is Physical Education teacher for class VII. Research data collection techniques using survey methods with observation, interviews, and documentation. Technical analysis of the data carried out includes data collection, data reduction, and drawing conclusions. The validity of the data in this study used data triangulation. The results showed that the success rate of the evaluation of online learning in class VII SMPN 2 Cilongok was marked by the presence of students participating in the online learning evaluation reaching 96.56%, the average score reaching 81.23, and the KKM completeness level of 91.81. %. The conclusion from the implementation of the online learning evaluation is said to be valid because the students did their own evaluation, and the results of the online evaluation did not change. The weakness of the online evaluation is that the internet network is often unstable, there are students who don't have cellphones and students don't have quotas, so it really interferes with the implementation of the online evaluation. The advantage is that the online evaluation process does not require paper to make questions, is practical and easy to correct.